The ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA TIPE PISA PADA MATERI CHANGE AND RELATIONSHIP - Fauzan Zulfendri, Ahmad; Yuhana, Yuyu; Hendraya, Aan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This descriptive qualitative research aimed to analyze the errors made by 11th-grade students (25 students) in solving 6 PISA-type word problems on the topic of